Water Safety Plans for Rural Water Supply in India : Policy Issues and Institutional Arrangements - Rouse, Michael; Pilgrim, Nicholas; Nair, Amit (World Bank, Washington, DC, 2017)
This report outlines the key principles of water safety planning for rural water supply in India. Water safety planning represents a change of emphasis from end-of-pipe testing to the management of risks of contamination from source to mouth. End-of-pipe testing is still necessary to verify that safe drinking water is being delivered. The focus of the report is on the policy issues concerning the adoption of water safety planning and the institutional arrangements (roles and responsibilities) needed to operationalize the approach. Recommendations are provided on demonstrating and implementing the approach to establish a full program. There are three objectives of this study: 1) to consider policies for the delivery of safe drinking water quality in rural areas; 2) to provide a framework in which the various functions associated with a change of emphasis towards managing risks to the safety of drinking water can be incorporated into existing institutional frameworks, in particular building on the initiatives already taken in India to improve monitoring and surveillance of drinking water quality; and 3) to suggest an approach to demonstrate and implement such a framework.